Program Edukasi Model Cibest sebagai Alat Peningkat Kesejahteraan di Lingkungan Pondok Pesantren Nurul Hakim Lombok, Kabupaten Lombok Barat - Irfan Syauqi Beik; Laily Dwi Arsyianti; Resfa Fitri; Rahmat Yanuar; Indah Fresma Sari; Muhamad Zidan; Muhamad Adzka Noor Sadaryun (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Prosperity can be achieved through poverty alleviation. One of the measuring tools for measuring the impact of poverty alleviation programs is the CIBEST Model. While the CIBEST model has been primarily used in the fields of zakat and waqf, this model still needs to be disseminated to other segments for a broader impact, including Islamic boarding schools. The community service program conducted at Pondok Pesantren Nurul Hakim aimed to enhance understanding of the application of the CIBEST model in pesantren. The methods used in this service were dissemination in the form of material presentations and assessments in the form of post-test. Program evaluation results showed that participants had a good level of understanding, with the highest score reaching 90. Participants gave positive feedback and suggested expanding the theoretical scope and increasing the program's socialization. The obstacle faced in the socialization was the limited time so that participants could study the material thoroughly. The signing of a Letter of Intent between IPB University and Pondok Pesantren Nurul Hakim was conducted as a strategic commitment to program sustainability. This step aims to ensure that the program can continue sustainably and provide long-term benefits. With continuous collaboration and ongoing development of program materials, it is hoped that this activity can have a broader impact on the community. Recommendations from this program include increasing socialization, developing program materials, and involving more parties to strengthen understanding of the CIBEST Model. It is hoped that this program can make a significant contribution to improving community welfare and empowering the pesantren community to implement it sustainably.